Odbiorca tłumaczenia w międzykulturowym treningu mediacyjnym (na przykładzie prac chińskich studentów polonistyki) - Kubicka, Emilia; Olkiewicz, Filip (Neofilolog, 2023)
The aim of this paper is to present and describe the development of textual mediation skills in the approach proposed by companion volume to Common European framework of reference for languages (CEFR CV) from 2018. The approach described in CEFR CV was applied during a translatology course dedicated to Chinese students of Polish language and culture, whose intersemiotic and intralingual translations are analyzed in this paper. According to Heinz Vater the ‘text’ is a linguistic (written or oral) phenomenon that comes into realization in the context and is understandable (complete) within a given situation. It should also be cohesive (grammatically correct) and coherent (semantic consistent). All these indicators of textuality turn out to be difficult for Chinese students, ranging from the lack of cohesion, through the lack of coherence, to the communicative dependence of the target text from the source text and not taking into account features of the target recipient. The authors focus on the latter aspect and discuss the ways of presenting in the student’s translations the world depicted in the source texts as well as protagonists. They point to successful (i.e., target recipient-oriented) and unsuccessful translation solutions and identify potential causes of disruptions in the mediation process.